Police cooperation in the European Union under the treaty of Lisbon: opportunities and limitations - Aden, Hartmut (Schriftenreihe des Arbeitskreises Europäische Integration e.V, 2015)
Police Cooperation in the EU before and after the Treaty of Lisbon : Continuity and Innovation / Hartmut Aden -- Revolution or Evolution through the Treaty of Lisbon : Police Cooperation in Europe in a Broader Historical Context / Cyrille Fijnaut -- Policy Making in Policing and Criminal Justice under Lisbon Rules : More Democratic, More Complex, and More Conflict-Prone / Daniela Kietz -- Before and after the Treaty of Lisbon : the Legal Framework of Police Cooperation in the EU compared / Daniela A. Heid -- Differentiated Integration : ever more relevant for Police Cooperation after the Treaty of Lisbon? / Funda Tekin -- Police Professionalism in the European Union / Monica den Boer -- Police Training and Police Studies in the EU Member States : towards Higher Standards by Coordination? / Hans-Gerd Jaschke -- Imbalances in an Expanding Research Area : the widely Neglected Practical Dimension of EU Internal Security Policy / Wilhelm Knelangen -- Do Council Instruments matter? : the Effect of Council Instruments on Practical Police Cooperation in the EU / Ludo Block -- European and International Cooperation in Practice : the Case of the Berlin Police / Bettina Rauch-Schulz -- Effective Cross-Border Knowledge Sharing between Police Forces - the German-Polish Police and Customs Cooperation Centre (PCCC) / Mario Gruschinske, Nathalie Hirschmann & Laura Füger -- Contributions of Member States to EU Police External Operations / Olivier Cahn -- Police Information Sharing and Data Protection in the European Union before and after the Treaty of Lisbon / Hartmut Aden -- Conflicts between Data Protection Harmonisation and a High Level of Protection: Shortcomings of the European Commission's Proposal for a Police and Justice Directive / Peter Schaar & Karsten Behn -- EU Police Cooperation and Information Sharing : more Influence for the European Parliament? / Jan Philipp Albrecht -- The Exchange of Information between Police Organisations in the EU under the Treaty of Lisbon - Routine and Difficulties from a Practical Perspective / Michael Niemeier -- Cooperation between the Private Sector and Law Enforcement Agencies : an Area in between Legal Regulations / Gertjan Boulet & Paul De Hert